Light rail investment for the future : 8th Joint Conference on Light Rail Transit, November 11-15, 2000, Dallas, Texas. - National Research Council (U.S.). Transportation Research Board; American Public Transportation Association; Joint Conference on Light Rail Transit 2000 : Dallas, Texas) ([Washington, D.C. : Transportation Research Board, National Research Council, 2000)
This CD-ROM includes 49 papers presented at the eighth in a series of light rail transit conferences jointly sponsored by the American Public Transportation Association and the Transportation Research Board. The CD-ROM also features an informative, full-color brochure,'This is Light Rail Transit.
System requirement: Adobe Acrobat Reader 4.0 or higher.
Disc characteristics: CD-ROM.
Windows 95/98/NT or Macintosh; CD-ROM drive.
Keywords: Street-railroads -- United States -- Congresses; Electric railroads -- United States -- Congresses